Response of Bacterial Community to the Occurrence of Clubroot Disease in Chinese Cabbage - Ni, Haiping; Zong, Rui; Sun, Jianjun; Wu, Yuxia; Yu, Lei; Liu, Yuanyuan; Liu, Jin; Ju, Ruicheng; Sun, Xianli; Zheng, Yulian; Tan, Lekun; Liu, Lumin; et al. (Frontiers in Microbiology, 2022)
Clubroot disease is a common soil-borne disease caused by Plasmodiophora brassicas Wor. and widely occurred in Chinese cabbage. Soil microorganisms play vital roles in the occurrence and development of plant disease. The changes in the soil bacterial community could indicate the severity of plant disease and provide the basis for its control. This study focused on the bacterial community of the clubroot disease-infected soil-root system with different severity aiming to reveal the composition and structure of soil bacteria and identified potential biomarker bacteria of the clubroot disease. In the clubroot disease-infected soil, the bacterial community is mainly composed of Actinobacteria, Gammaproteobacteria, Alphaproteobacteria, Bacilli, Thermolrophilia, Bacteroidia, Gemmatimonadetes, Subgroup_6, Deltaproteobacteria, KD4-96, and some other classes. While the major bacterial classes in the infected roots were Oxyphotobacteria, Gammaproteobacteria, Alphaproteobacteria, Actinobacteria, Bacilli, Bacteroidia, Saccharimonadia, Thermoleophilia, Clostridia, Chloroflexia, and some other classes. The severe clubroot disease soil-root system was found to possess a poorer bacterial richness, evenness, and better coverage. Additionally, a significant difference was observed in the structure of the bacterial community between the high severity (HR) and low severity (LR) soil-root system. Bacillus asahii and Noccaea caerulescens were identified as the differential bacteria between the LR and HR soil and roots, respectively. pH was demonstrated as a vital factor that was significantly associated with the abundance of Bacillus asahii and Noccaea caerulescens. This study provides novel insight into the relationship between soil bacteria and the pathogen of clubroot disease in Chinese cabbage. The identification of resistant species provides candidates for the monitoring and biocontrol of the clubroot disease.